2003
DOI: 10.1039/b212423h
|View full text |Cite
|
Sign up to set email alerts
|

Titanium dipyrrolylmethane derivatives: rapid intermolecular alkyne hydroamination

Abstract: Alkynes are rapidly hydroaminated by primary amines using titanium dipyrrolylmethane derivatives as catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(69 citation statements)
references
References 26 publications
3
66
0
Order By: Relevance
“…The first catalyst described for this 3-component coupling reaction was TiA C H T U N G T R E N N U N G (NMe 2 ) 2 A C H T U N G T R E N N U N G (dpma), [12] where dpma [13] = N,N-di(pyrrolyl-a-methyl)-N-methylamine. More recently, we have found that TiA C H T U N G T R E N N U N G (NMe 2 ) 2 A C H T U N G T R E N N U N G (dpm), [14] where dpm [15] = 5,5-dipyrrolylmethane, is a quite active catalyst for alkyne iminoamination.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first catalyst described for this 3-component coupling reaction was TiA C H T U N G T R E N N U N G (NMe 2 ) 2 A C H T U N G T R E N N U N G (dpma), [12] where dpma [13] = N,N-di(pyrrolyl-a-methyl)-N-methylamine. More recently, we have found that TiA C H T U N G T R E N N U N G (NMe 2 ) 2 A C H T U N G T R E N N U N G (dpm), [14] where dpm [15] = 5,5-dipyrrolylmethane, is a quite active catalyst for alkyne iminoamination.…”
Section: Resultsmentioning
confidence: 99%
“…C NMR spectra were recorded on VXR-500 spectrometers. Melting points were measured on a Mel-Temp II apparatus with a mercury thermometer and are uncalibrat- [14] and TiA C H T U N G T R E N N U N G (dpma)A C H T U N G T R E N N U N G (NMe 2 ) 2 (1) [12] were made following the literature procedures. Alkynes were purchased either from Sigma-Aldrich Co. or from GFS chemicals and dried from CaO under dry nitrogen.…”
Section: Experimental Section General Considerationsmentioning
confidence: 99%
“…[65][66][67][68] Following an initial report of titanium catalyzed hydroamination by Rothwell and coworkers, [69] research into hydroamination catalysis has also followed the trend of focusing on Cp-based ligand systems and then moving onto non-Cp-based catalysts. A variety of systems have been developed for hydroamination reactions including work from the groups of Bergman, [15,64,[70][71][72][73] Livinghouse, [74,75] Odom, [67,[76][77][78][79][80][81] Beller, [65,[82][83][84][85][86] Doye, [87][88][89][90][91][92][93][94] ourselves, [59,61,62,95,96] and others. [11,[97][98][99][100][101][102][103][104]…”
Section: Hydroamination Catalysismentioning
confidence: 99%
“…[44] Odom and coworkers have compared the activity of complex 1 with a series of other titanium complexes as precata-lysts for intermolecular alkyne hydroamination; they found that it has a lower activity than the commercially available Ti(NMe 2 ) 4 . [45] Beckhaus and coworkers have published very recently a series of excellent examples of molecular self-organization. The selective formation of polynuclear titanium complexes was realized in the reactions of 1 and 3 with different Nheterocyclic compounds [46,47] by directed reduction of sixmembered nitrogen heterocycles and molecular self-organization (Scheme 12).…”
Section: New Reactionsmentioning
confidence: 99%